169k views
1 vote
How do you do this question?

How do you do this question?-example-1
User Ticallian
by
5.4k points

1 Answer

1 vote

Answer:

0

Convergent

Explanation:

aₙ = 2ⁿ / n!

aₙ₊₁ = 2ⁿ⁺¹ / (n+1)!

lim(n→∞)│(2ⁿ⁺¹ / (n+1)!) / (2ⁿ / n!)│

lim(n→∞)│(2ⁿ⁺¹ / (n+1)!) × (n! / 2ⁿ)│

lim(n→∞)│(2ⁿ⁺¹ / 2ⁿ) × (n! / (n+1)!)│

Notice that (n+1)! = (n+1) n!. So this reduces to:

lim(n→∞)│2 × 1 / (n+1)│

0

The limit is less than 1, so the series is absolutely convergent.

User Wojjas
by
5.9k points